Current trends in art and design for paediatric wellness in built environments (2020–2025): a thematic review - Zairul, Mohd; Hafizah, Noor (Frontiers in Pediatrics, 2026)
Art and design interventions are increasingly recognized as necessary for paediatric wellness in built environments (e.g., hospitals and schools). However, current literature is fragmented, lacking a holistic integration of design strategies to address children's psychological, sensory, and physical needs. This review addresses that gap by systematically examining recent studies linking design strategies to paediatric well-being. We aimed to identify prevailing trends and themes in publications from 2020 to 2025. Using a systematic thematic review approach (TreZ), we searched Scopus, Web of Science, and Google Scholar, identifying 25 relevant studies after applying strict inclusion criteria. Five major thematic domains emerged: (1) biophilic and nature-based design, (2) playful and interactive environments, (3) sensory and emotional design, (4) inclusive and family-centred design, and (5) aesthetic, cultural, and identity-oriented design. The findings reveal a lack of interdisciplinary integration and limited empirical validation of current design approaches. This review underscores the need for cross-thematic integration, greater child participation in design, rigorous post-occupancy evaluation, and exploration of smart technologies to create more restorative, health-supportive environments for children.